Electrogenerated Conductive Polymers from Triphenylamine End-Capped Dendrimers - Mangione, Maria Ines (2013)
Electroactive end-capped dendritic macromolecules were designed and synthesized. Their structures contain triphenylamine moieties as part of the core or dendrons. The electrogenerated films produced with these monomers behaved as conductive dendritic polymers that can be reversible charged, both in the core and in the peripheral units. The design of dendrimer structures with the introduction of systematic changes allows to establish relationships between their electro-optical properties with molecular structural parameters. The films of polymeric material hold good electrical conductivity, reversible electrochemical processes and chemical stability. The results indicate that the use of conjugated and rigid structures in dendritic macromolecules is an important factor in order to obtain electropolymeric films. This work provides a model to design starburst dendrimers capable to form electrochemically active polymers with potential applications in electronic and optoelectronic devices.